High-Impact Details of Play and Movements in Female Basketball Game - Nagano, Yasuharu; Sasaki, Shogo; Shimada, Yui; Koyama, Takeshi; Ichikawa, Hiroshi (Sports Medicine International Open, 2021)
This study aimed to identify the high-impact details of play and movements with higher acceleration and their frequency during a female basketball match. Trunk acceleration was measured during a simulated basketball game with eight female players. The extracted instance was categorized, which generated at > 6 and 8 G resultant accelerations using a video recording and an accelerometer attached to the players’ trunk, as details of play and movements. The frequency and ratio of the details of play and movements regarding all detected movements were calculated. A total of 1062 and 223 play actions were detected for the resultant acceleration thresholds of > 6 and 8 G, respectively. For these acceleration thresholds, in terms of details of play, positioning on the half-court was the most frequently observed (29.6 and 23.8%, respectively). In terms of movements, deceleration was the most frequently detected movement (21.5 and 23.3%, respectively), followed by landing (7.6 and 15.7%, respectively). Deceleration during positioning on the half-court and defense as well as landing mostly after a shot were detected as high-impact frequent basketball-specific movements. The results also showed that characteristics of movements or playing style and playing position may have an effect on acceleration patterns during a basketball game.
Keywords: measurement; musculoskeletal; quantitative study